Prediction of outcome following hypoxia/ischaemia in the human infant using cerebral impedance - Lingwood, B.; Healy, Genevieve; Kecskes, Z.; Dunster, K.; Gray, P.; Ward, L.; Colditz, P. (Elsevier Ireland Ltd, 2009)
Objective: Changes in cerebral impedance in the newborn piglet are able to discriminate, within 1-2 h of acute hypoxia, between animals which will have a good neurological outcome, and those who have suffered more severe hypoxia resulting in poor outcome. The aim of this study was to determine if cerebral impedance could be used to identify those human infants with an encephalopathy following acute hypoxia who subsequently have a poor neurological outcome. It is these infants who may benefit most from neural rescue treatment. Methods: Twenty-four newborn term infants with evidence of severe acute intrapartum hypoxia and encephalopathy were studied. Bioimpedance spectroscopy was commenced as soon as possible after birth and repeated every 30 min until the infant was 12 h old. Neurodevelopmental outcome was assessed at 12 months of age. Results: Although cerebral impedance was different to control values, there was no significant difference in cerebral impedance between hypoxic babies with normal and those with abnormal development. Conclusion: Cerebral impedance was increased in hypoxic babies, as predicted from animal data, but the method was not suitable for discrimination of outcome. Significance: Cerebral impedance is not useful for early identification of infants who subsequently have a poor outcome after acute intrapartum hypoxia and who may benefit from neural rescue treatment. © 2008 International Federation of Clinical Neurophysiology.